In sickness and in health: The impact of personnel changes and public leaders’ personalities for healthcare employees’ sickness absence, job and leadership satisfaction - Gøtzsche-Astrup , Oluf; Gottlieb, Troels (Politica, 2021)
Redundancy and staff expansions in the public sector are events associated with employee uncertainty and potential work-related stress. It is therefore essential for public leaders to be aware of potential consequences for such changes in employee units. We explore the relationship between redundancies, staff expansions and leadership personality on the one hand and long-term sickness leave, job satisfaction and leader satisfaction on the other hand among 146 head nurses and their 3426 employees in Hospitals in the Capital Region of Denmark. We find that redundancies are associated with higher levels of long-term sickness leave. Staff expansions are related to lower levels of illness and higher leader satisfaction ratings. Leaders who are more emotionally stable have employees with higher job and leader satisfaction.